A method for preparing β-SiC powder
The orchid charcoal and water glass were mixed on the molecular scale by hydrothermal method to form a carbon-silicon composite precursor, and a carbon-heat reduction reaction was carried out at high temperature, which solved the problems of high raw material purity and equipment corrosion in the preparation of β-SiC powder, and achieved the preparation of β-SiC powder with high yield and high purity.
Patent Information
- Application Number
- CN202310093663.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-07
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-02-07
AI Technical Summary
The existing β-SiC powder preparation methods have problems such as high purity of raw materials, high energy consumption and low product purity. The alkaline substances in water glass will corrode the equipment under high temperature conditions, affecting industrialization implementation.
The hydrothermal method is used to mix the orchid, water glass and organic acid evenly to form a carbon-silicon composite precursor. Then, the carbon-heat reduction reaction is carried out under an argon atmosphere to obtain a β-SiC powder and purify it by calcination and acid-base treatment.
The yield and purity of β-SiC powder is improved, the requirements for raw material purity are reduced, the equipment corrosion problems are reduced, and the industrialization of technology is conducive to the industrialization of technology.
Smart Images

Figure CN116102016B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of carbide materials, and in particular to a method for preparing β-SiC powder. Background Art
[0002] Lignite is a solid carbon product obtained by low-temperature dry distillation of non-viscous or weakly viscous high-volatile bituminous coal. It has the characteristics of high fixed carbon and low volatile matter. It is mostly used as a solid fuel, with lignite as a raw material for further processing and utilization. Due to its poor surface activity, how to expand the downstream application market of lignite, change the relatively single downstream structure, and realize the high-value utilization of lignite is a technical problem that needs to be solved urgently.
[0003] Water glass, also known as soluble glass, is a metal silicate material that is soluble in water and is composed of alkali metal oxides and silicon dioxide. As a secondary resource rich in silicon components, water glass is widely used in many fields due to its low price compared with silica sol, metallic silicon and silica sand. However, since water glass contains alkali metal oxides, these metal oxides are strongly alkaline and will sublimate under high temperature conditions, which will cause certain corrosion to the equipment and seriously affect the service life of the equipment.
[0004] As an advanced ceramic material, β-SiC has attracted great attention in recent years.
[0005] For the preparation of β-SiC, researchers have developed many new synthesis methods, including: sol-gel method, polymer pyrolysis method, plasma method, laser method, chemical vapor deposition method, etc. Although these methods can prepare β-SiC, they are subject to certain limitations in industrial production due to the complex process methods or expensive raw materials.
[0006] Chinese patent CN1210204C, a method for preparing silicon carbide, is to mix water glass with a carbon source, add water or a surfactant for homogenization to obtain a precursor, calcine the precursor at 1400~1800℃ for 0.5~4h in a non-oxidizing atmosphere, and then remove the residual carbon at a temperature below 800℃ in an air atmosphere to obtain silicon carbide. This method uses water glass as a silicon source. Since Na2O in water glass will sublime at around 1200℃, the strongly alkaline Na2O will corrode high-temperature equipment under high temperature conditions, seriously affecting the service life of the equipment, and industrialization is difficult.
[0007] Deng Lirong et al. (Multi-heat source vacuum synthesis of high-purity, high-density, large-particle size 3C-SiC micropowder [J], China Powder Technology, 2020, 26(2): 29-34) prepared β-SiC micropowder using micron-grade silicon raw materials and carbonaceous materials with purities of 99wt% and 90.87wt%, respectively. Due to the high purity of the selected raw materials, the production cost is relatively high. In addition, this method is a direct mixing of solid-solid raw materials, which cannot ensure that the carbon source and the silicon source are mixed evenly so that the two can obtain the maximum contact area, which will affect the yield of β-SiC micropowder. Summary of the invention
[0008] In view of the common problems of high raw material purity, high energy consumption and low product purity in the preparation method of β-SiC powder in the prior art, the purpose of the present invention is to provide a preparation method of β-SiC powder, which not only solves the problem of high raw material purity required for the preparation of β-SiC powder, but also improves the yield of β-SiC powder product, reduces the problem of water glass corrosion to equipment, and is conducive to the industrial implementation of the technology.
[0009] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0010] A method for preparing β-SiC powder comprises the following steps:
[0011] Adding blue carbon, water glass, organic acid and metal salt into water, mixing evenly and then performing hydrothermal treatment at a constant temperature of 100-200° C. for 1-10 hours to obtain a carbon-silicon composite precursor;
[0012] The carbon-silicon composite precursor is placed in an argon atmosphere, and subjected to a carbon thermal reduction reaction at 1300-1800° C. for 1-20 hours to obtain a reaction product, which is then purified to obtain β-SiC powder.
[0013] Furthermore, the organic acid is one or more of tartaric acid, oxalic acid, malic acid, citric acid and ascorbic acid.
[0014] Furthermore, the modulus of water glass is 1.5~3.5.
[0015] Furthermore, the molar ratio of water glass to silicon carbon in semi-coke is 1:(1-8).
[0016] Furthermore, the molar ratio of the metal salt to the silicon in the water glass is 0.01-5:1.
[0017] Furthermore, the molar ratio of silicon to organic acid in water glass is 1:(0.1-1).
[0018] Furthermore, the metal salt is one of ferric chloride, nickel chloride and cobalt chloride.
[0019] Furthermore, the specific process of purifying the reaction product is: roasting the reaction product to remove unreacted carbon, then using hydrochloric acid to remove unreacted metal salts, and then soaking in an alkaline solution to remove excess silicon dioxide.
[0020] Furthermore, the calcination temperature is 500-900°C and the calcination time is 1-6h.
[0021] Furthermore, the alkali is one or two of sodium hydroxide, potassium hydroxide and calcium hydroxide; the concentration of the alkali solution is 1-6 mol / L, and the soaking time is 6-24h.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] Although water glass is widely available and is a soluble alkali metal silicate material, it is corrosive and can easily corrode equipment. Blue charcoal is cheap, but has poor surface activity and is difficult to fully contact and crosslink with water glass. The present invention uses a hydrothermal method to fully crosslink and mix water glass and blue charcoal at a molecular scale to form a carbon-silicon composite precursor complex, thereby significantly improving the yield of silicon carbide. Since this method can achieve the mixing of raw materials at a molecular scale, the requirements for raw material purity can be reduced. Organic acids are added during the crosslinking and mixing process to neutralize the alkaline substances in the water glass, thereby reducing the cost of equipment corrosion depreciation. Water glass and blue charcoal are evenly mixed in a liquid phase, and the prepared precursor has the advantages of simple operation, short preparation cycle, and low reaction temperature, which is conducive to the large-scale production of β-SiC powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the X-ray diffraction spectrum of the β-SiC powder obtained in Example 1 of the present invention.
[0025] Figure 2 This is the X-ray diffraction spectrum of the β-SiC powder obtained in Example 2 of the present invention.
[0026] Figure 3 This is the X-ray diffraction spectrum of the β-SiC powder obtained in Example 3 of the present invention.
[0027] Figure 4 This is a photo of the furnace after the reaction of Example 2 of the present invention.
[0028] Figure 5 This is a photo of the furnace after the reaction of Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0029] The present invention will be described in detail below by way of embodiments in conjunction with the accompanying drawings.
[0030] The present invention uses blue carbon and water glass as raw materials, prepares a precursor compound by a hydrothermal method combined with an organic acid treatment, and further prepares β-SiC powder. Specifically, a method for preparing β-SiC powder includes the following steps:
[0031] (1) Preparation of silicon carbide precursor: Add blue charcoal, water glass, organic acid and metal salt into water, mix them evenly and place them in a hydrothermal reactor. The molar ratio of water glass to silicon carbon in blue charcoal is 1: (1-8), the molar ratio of metal salt to silicon in water glass is 0.01-5:1, and the molar ratio of silicon in water glass to organic acid is 1: (0.1-1). Then, hydrothermal treatment is carried out at a constant temperature of 100-200°C for 1-10 h. After cooling to room temperature, filter and place in an oven at 50-120°C for 5-24 h to obtain a carbon-silicon composite precursor. Wherein, the metal salt is one of ferric chloride, nickel chloride and cobalt chloride.
[0032] The organic acid is one or more of tartaric acid, oxalic acid, malic acid, citric acid and ascorbic acid.
[0033] The modulus of water glass is 1.5~3.5.
[0034] Blue charcoal has poor surface activity and is difficult to form a uniform complex with water glass. Hydrothermal treatment at a certain temperature is used to crosslink blue charcoal and water glass to form a sufficient mixture at the molecular scale, thereby increasing the yield of β-SiC powder. The present invention adopts a liquid phase reaction, so there is no requirement for the purity of the raw materials.
[0035] (2) Carbothermal reduction: In a high-temperature furnace, collect the carbon-silicon composite precursor, place it in an argon atmosphere, and heat it to 1300-1800°C for a carbothermal reduction reaction for 1-20 hours. After the reaction, cool it naturally to room temperature to obtain a reaction product.
[0036] Water glass is alkaline and can corrode production equipment such as high-temperature furnace refractory materials. During the hydrothermal treatment process, organic acids are added for regulation, thereby extending the service life of equipment consumables during the carbon thermal reduction process.
[0037] (3) Silicon carbide purification:
[0038] ① Carbon removal process: The reaction product is calcined at 500-900℃ for 1-6h to remove unreacted carbon.
[0039] ② Silicon removal process: First, use hydrochloric acid to remove the added metal salt, then soak in an alkaline solution with a concentration of 1-6 mol / L for 6-24 hours to remove excess silicon dioxide, and finally wash, filter and dry to obtain β-SiC powder.
[0040] Wherein, the alkali is one or two of sodium hydroxide, potassium hydroxide and calcium hydroxide.
[0041] Example 1
[0042] Water glass (Na2O·1.0SiO2), blue carbon, organic acid (tartaric acid) and ferric chloride were added into water, mixed evenly and placed in a hydrothermal reactor, kept at 100°C for 5 hours, cooled to room temperature, filtered, and dried at 80°C for 12 hours to obtain a carbon-silicon composite precursor, wherein the molar ratio of silicon to carbon was 1:4, the molar ratio of ferric chloride to silicon was 0.05:1, and the molar ratio of silicon to organic acid was 1:0.2.
[0043] In a high-temperature furnace, the carbon-silicon composite precursor is placed in an argon atmosphere and calcined at 1300° C. for 10 hours. After the reaction is completed, it is naturally cooled to room temperature to obtain a reaction product.
[0044] The reaction product was heated at 500 °C for 6 h to remove unreacted carbon.
[0045] First, hydrochloric acid was used to remove the added metal salt catalyst, and then a NaOH solution with a concentration of 1.5 mol / L was used to soak for 24 hours to remove unreacted silica. Finally, β-SiC powder was obtained by washing, filtering and drying. The yield of β-SiC powder was 85.4% and the purity was 99.5%. No corrosion or cracks were found in the high-temperature furnace refractory materials.
[0046] from Figure 1 It can be seen that the product obtained in Example 1 is β-SiC.
[0047] Example 2
[0048] Water glass (Na2O·2.5SiO2), blue carbon, organic acid (oxalic acid) and nickel chloride were added into water, mixed evenly and placed in a hydrothermal reactor, kept at 150°C for 3 hours, cooled to room temperature and filtered, and dried at 100°C for 8 hours to obtain a carbon-silicon composite precursor, wherein the molar ratio of silicon to carbon was 1:5.5, the molar ratio of ferric chloride to silicon was 0.5:1, and the molar ratio of silicon to organic acid was 1:0.5.
[0049] In a high-temperature furnace, the carbon-silicon composite precursor is placed in an argon atmosphere and calcined at 1500° C. for 8 hours. After the reaction is completed, it is naturally cooled to room temperature to obtain a reaction product.
[0050] The reaction product was heated at 700 °C for 4 h to remove unreacted carbon.
[0051] First, hydrochloric acid was used to remove the added metal salt catalyst, and then a KOH solution with a concentration of 2.5 mol / L was used to soak for 15 hours to remove unreacted silica. Finally, β-SiC powder was obtained by washing, filtering and drying. The yield of β-SiC powder was 87.8% and the purity was 99.58%. No corrosion or cracks were found in the high-temperature furnace refractory materials.
[0052] from Figure 2 It can be seen that the product obtained in Example 2 is β-SiC.
[0053] Example 3
[0054] Water glass (Na2O·3.5SiO2), blue carbon, organic acid (malic acid) and ferric chloride were added into water, mixed evenly and placed in a hydrothermal reactor, kept at 200°C for 5 hours, cooled to room temperature, filtered, and dried at 120°C for 5 hours to obtain a carbon-silicon composite precursor, wherein the molar ratio of silicon to carbon was 1:7, the molar ratio of ferric chloride to silicon was 1.0:1, and the molar ratio of silicon to organic acid was 1:0.8.
[0055] In a high-temperature furnace, the carbon-silicon composite precursor is placed in an argon atmosphere and calcined at 1750° C. for 4 hours. After the reaction is completed, it is naturally cooled to room temperature to obtain a reaction product.
[0056] The reaction product was heated at 900 °C for 2 h to remove unreacted carbon.
[0057] First, hydrochloric acid was used to remove the added metal salt catalyst, and then a 4 mol / L Ca(OH)2 solution was used to soak for 6 hours to remove unreacted silica. Finally, β-SiC powder was obtained by washing, filtering and drying. The yield of β-SiC powder was 89.6%, the purity was 99.72%, and no corrosion or cracks were found in the high-temperature furnace refractory materials.
[0058] from Figure 3 It can be seen that the product obtained in Example 3 is β-SiC.
[0059] Example 4
[0060] Water glass (Na2O·2SiO2), blue carbon, organic acid (mixture of citric acid and ascorbic acid) and ferric chloride were added into water, mixed evenly and placed in a hydrothermal reactor, kept at 120°C for 10 hours, cooled to room temperature, filtered, and dried at 50°C for 24 hours to obtain a carbon-silicon composite precursor, wherein the molar ratio of silicon to carbon was 1:8, the molar ratio of ferric chloride to silicon was 5:1, and the molar ratio of silicon to organic acid was 1:1.
[0061] The carbon-silicon composite precursor was placed in an argon atmosphere and calcined at 1800° C. for 1 hour. After the reaction was completed, it was naturally cooled to room temperature to obtain a reaction product.
[0062] The reaction product was heated at 600 °C for 6 h in a high temperature furnace to remove unreacted carbon.
[0063] First, the added metal salt catalyst was removed with hydrochloric acid, and then the unreacted silicon dioxide was removed by soaking in an alkaline solution for 10 hours. The alkali was a mixture of sodium hydroxide and potassium hydroxide, and the total concentration of sodium hydroxide and potassium hydroxide was 6 mol / L. Finally, β-SiC powder was obtained by washing, filtering and drying. No corrosion or cracks appeared in the high-temperature furnace refractory materials.
[0064] Example 5
[0065] Water glass (Na2O·3SiO2), blue carbon, organic acid (ascorbic acid) and ferric chloride were added into water, mixed evenly and placed in a hydrothermal reactor, kept at 200°C for 1 hour, cooled to room temperature, filtered, and dried at 70°C for 15 hours to obtain a carbon-silicon composite precursor, wherein the molar ratio of silicon to carbon was 1:1, the molar ratio of ferric chloride to silicon was 0.01:1, and the molar ratio of silicon to organic acid was 1:0.1.
[0066] In a high-temperature furnace, the carbon-silicon composite precursor is placed in an argon atmosphere and calcined at 1300° C. for 20 hours. After the reaction is completed, it is naturally cooled to room temperature to obtain a reaction product.
[0067] The reaction product was heated at 800 °C for 1 h to remove unreacted carbon.
[0068] First, the added metal salt catalyst was removed with hydrochloric acid, and then the unreacted silica was removed by immersion in a 4 mol / L Ca(OH)2 solution for 20 hours. Finally, β-SiC powder was obtained by washing, filtering and drying. No corrosion or cracks were found in the high-temperature furnace refractory materials.
[0069] The yield of β-SiC powder in the present invention is as high as 89.6%.
[0070] Comparative Example 1
[0071] Water glass (Na2O·2.5SiO2), blue charcoal and organic acid (oxalic acid) were added into water, mixed evenly and placed in a hydrothermal reactor, kept at 150°C for 3 hours, cooled to room temperature and filtered, and dried at 100°C for 8 hours to obtain a carbon-silicon composite precursor, wherein the molar ratio of silicon to carbon was 1:5.5, and the molar ratio of silicon to organic acid was 1:0.5.
[0072] In a high-temperature furnace, the carbon-silicon composite precursor is placed in an argon atmosphere and calcined at 1500° C. for 8 hours. After the reaction is completed, it is naturally cooled to room temperature to obtain a reaction product.
[0073] The reaction product was heated at 700 °C for 4 h to remove unreacted carbon.
[0074] First, impurities were removed with hydrochloric acid, and then the unreacted silica was removed by soaking in a 2.5 mol / L KOH solution for 15 hours. Finally, β-SiC powder was obtained by washing, filtering and drying. The yield of β-SiC powder was 78.5%, the purity was 99.52%, and no corrosion or cracks were found in the high-temperature furnace refractory materials.
[0075] From the comparison of the yields of Example 2 containing soluble metal salts and Comparative Example 1 without metal salts, it can be seen that the metal salt can play a catalytic role, thereby improving the yield of β-SiC powder.
[0076] Comparative Example 2
[0077] Sodium carbonate (Na2O·2.5SiO2), blue carbon and nickel chloride were added into water to mix evenly and placed in a hydrothermal reactor, kept at 150°C for 3 hours, cooled to room temperature, filtered, and dried at 100°C for 8 hours to obtain a carbon-silicon composite precursor, wherein the molar ratio of silicon to carbon was 1:5.5, and the molar ratio of ferric chloride to silicon was 0.5.
[0078] In a high-temperature furnace, the carbon silicon precursor is placed in an argon atmosphere and calcined at 1500° C. for 8 hours. After the reaction is completed, it is naturally cooled to room temperature to obtain a reaction product.
[0079] The reaction product was heated at 700 °C for 4 h to remove unreacted carbon.
[0080] The added metal salt catalyst was first removed with hydrochloric acid, and then the unreacted silica was removed by soaking in a 2.5 mol / L KOH solution for 15 h. Finally, β-SiC was obtained by washing, filtering and drying. The yield of β-SiC powder was 87.6% and the purity was 99.53%.
[0081] See also Figure 4 and Figure 5 , Comparative Example 2 and Example 2 ( Figure 4 ), in this comparative example 2, no organic acid is added for regulation, and the alkaline substances in the water glass cause serious corrosion or even falling of the refractory materials in the furnace of the high-temperature equipment. This shows that adding organic acid for regulation during the precursor preparation process is crucial to extending the service life of the high-temperature equipment.
Claims
1. A method for preparing β-SiC powder, characterized in that: The following steps are involved: Adding blue carbon, water glass, organic acid and metal salt into water, mixing evenly and then performing hydrothermal treatment at a constant temperature of 100-200° C. for 1-10 h to obtain a carbon-silicon composite precursor; Placing the carbon-silicon composite precursor under an argon atmosphere for a carbon thermal reduction reaction for 1-20 hours to obtain a reaction product, and purifying the reaction product to obtain β-SiC powder; The organic acid is one or more of tartaric acid, oxalic acid, malic acid, citric acid and ascorbic acid; The molar ratio of silicon to organic acid in water glass is 1:(0.1-1); The modulus of water glass is 1.5~3.5; The temperature of the carbon thermal reduction reaction is 1300-1800°C and the time is 1-20h; The specific process of purifying the reaction product is: roasting the reaction product to remove unreacted carbon, then using hydrochloric acid to remove unreacted metal salts, and then soaking in an alkaline solution to remove excess silicon dioxide; The calcination temperature is 500-900°C and the calcination time is 1-6h; The metal salt is one of ferric chloride, nickel chloride and cobalt chloride.
2. The method for preparing β-SiC powder according to claim 1, characterized in that: The molar ratio of silicon to carbon in water glass and semi-coke is 1:(1-8).
3. The method for preparing β-SiC powder according to claim 1, characterized in that: The molar ratio of the metal salt to the silicon in the water glass is 0.01-5:
1.
4. The method for preparing β-SiC powder according to claim 1, characterized in that: The alkali is one or two of sodium hydroxide, potassium hydroxide and calcium hydroxide; the concentration of the alkali solution is 1-6 mol / L, and the soaking time is 6-24 hours.
Citation Information
Patent Citations
Method for preparing silicon-carbide
CN1210204C
Green method for preparing beta-silicon carbide with high specific surface area
CN113666375A
Method of preparing nano-silicon carbide fiber
CN1569626A